2016
DOI: 10.1001/jamaoncol.2016.0339
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Estrogen Receptor and Human Epidermal Growth Factor Receptor-2 Levels on the Efficacy of Trastuzumab

Abstract: clinicaltrials.gov Identifier: NCT00045032.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 24 publications
1
53
0
Order By: Relevance
“…Another (N9831) trial conducted during March 2002 to April 2005 revealed that the benefit from trastuzumab mainly relies upon IHC or FISH HER2 testing, irrespective of the degree of amplification . However, in a secondary analysis of the HERA trial with a median follow‐up time of 8 years, ER‐positive patients with a low ISH ratio (≥2 to <5) derived significantly less benefit from adjuvant trastuzumab therapy . This indicates that a longer follow‐up time may be necessary to accurately assess the benefits from anti‐HER2 treatment in such a group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another (N9831) trial conducted during March 2002 to April 2005 revealed that the benefit from trastuzumab mainly relies upon IHC or FISH HER2 testing, irrespective of the degree of amplification . However, in a secondary analysis of the HERA trial with a median follow‐up time of 8 years, ER‐positive patients with a low ISH ratio (≥2 to <5) derived significantly less benefit from adjuvant trastuzumab therapy . This indicates that a longer follow‐up time may be necessary to accurately assess the benefits from anti‐HER2 treatment in such a group.…”
Section: Discussionmentioning
confidence: 99%
“…15 However, in a secondary analysis of the HERA trial with a median follow-up time of 8 years, ER-positive patients with a low ISH ratio (≥2 to <5) derived significantly less benefit from adjuvant trastuzumab therapy. 7 This indicates that a longer follow-up time may be necessary to accurately assess the benefits from anti-HER2 treatment in such a group. In our hormone-receptorpositive subgroup, patients with a low ISH ratio tumour displayed a worse outcome (Table S5), which is consistent with the findings from the HERA trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An initial proteogenomic focus on ERBB2 is readily justified given the biological variability within tumors designated ERBB2 "positive". The testing guidelines are designed to offer as many patients anti-ERBB2 treatment as possible, even though it is recognized that this "catch all" approach likely includes a number of true-negative cases that do not benefit from these treatments 39 . Our analysis is not intended to be definitive or clinically actionable as the sample size is small and our pipeline is research-based.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccines that generate antibody responses using carrier proteins may require cumbersome recombinant protein production and chemical conjugation processes, which can be costly, lead to batch-to-batch variability, and elicit off-target antibody responses against other T and B cell epitopes on the carrier protein itself [36] . To circumvent this issue, we designed peptide constructs that incorporate a promiscuous T-helper cell epitope derived from measles virus fusion protein oncogenic protein HER2/neu, a surface receptor that has been successfully targeted by monoclonal antibodies for the treatment of Her2 + breast and gastric cancer [37] . To specifically induce therapeutic antibodies, we used Her2613-626 as the B-cell epitope, as it is within the portion of the Finally, we investigated the anti-GnRH response generated against a synthetic MVFGnRH peptide antigen, comparing our MSR technology with a bolus vaccine and MVFGnRH formulated in the gold standard adjuvant Alum.…”
Section: Broad Potential Of Msr For Vaccination Against Small Moleculmentioning
confidence: 99%